Kazakh musical and poetic art in the context of globalization - Akimzhanov B, Sultanova A, Zhamanbalinov Y, Omarova A., Kaztuganova A, (Opción, 2020)
The Kazakh people have a rich heritage which is finely described in their music, songs and poetry. Kazakh history, the national challenges, the battles for justice and freedom, and Kazakh personal joys and sorrows have been preserved over the centuries by Kazakhstan’s great composers and writers, giving the Kazakh people a deep understanding of their culture and traditions. But it is not just thing from their history; the traditional styles of music continue to be evolved and performed which is evidence of the pride the Kazakh people have in their culture. This study aims to analyze the song traditions of the Kazakh culture and to examine the latest Anthology of Kazakh music.